Mechanical, morphological and rheological properties of polyamide 6/organo-montmorillonite nanocomposites (eXPRESS Polymer Letters, 2007)
Polyamide (PA6) nanocomposites containing 4wt% organo-montmorillonite (OMMT) were melt-compounded followed by injection molding. The mechanical properties of the PA6/OMMT nanocomposites were studied through tensile and flexural tests. The rheological behaviour of the nanocomposites was determined by plate/plate rheological measurements. Attempts were made to trace the rheological parameters that reliably reflect the observed changes in the clay dispersion. X-ray diffraction (XRD) and atomic force microscopy (AFM) were used to characterize the exfoliation and dispersion of the OMMT in the PA6 matrix. The thermal properties of PA6/OMMT nanocomposite were characterized by Dynamic Mechanical Thermal Analysis (DMTA). The tensile modulus and strength of the PA6 was increased in the presence of OMMT. The flexural strength of PA6/OMMT was approximately doubled compared to the tensile strength value. The significant enhancement of both tensile and flexural strength was attributed to the delaminated clay formation. XRD and AFM results revealed the formation of PA6 nanocomposites as the OMMT was successfully exfoliated.